If this isn't nice, what is? the graduation speeches and other words to live by - Vonnegut, Kurt 1922-2007 (Seven Stories Press, 2020)
"Best known as one of our most astonishing and enduring contemporary novelists, Kurt Vonnegut was also a celebrated commencement address giver. He himself never graduated college, so his words to any class of graduating seniors always carried the delight, and gentle irony, of someone savoring an achievement he himself had not had occasion to savor on his own behalf. Selected and introduced by fellow novelist and friend Dan Wakefield, the speeches in "If This Isn't Nice, What Is?" capture this side of Kurt Vonnegut for the first time in book form. In each of these talks Vonnegut takes pains to find the few things worth saying and a conversational voice to say them in that isn't heavy-handed or pretentious or glib, but funny and serious and joyful even if sometimes without seeming so"--
Keywords: Bakkalaureus; Studienabschluss; USA; Speeches, addresses, etc., American; Baccalaureate addresses; Rede